Retrograde colon intussusception in an adult due to adenoma: Treatment by combined laparoscopic and endoscopic approach. Issue 4 (28th October 2013) - Shibahara, Kotaro; Ueda, Masanobu; Takai, Maki; Sonoda, Kozo; Yoshida, Michio; Maekawa, Soichiro
Abstract This report describes the case of a young patient who underwent laparoscopic surgery to reduce for a retrograde intussusception of the sigmoid‐descending colon caused by adenoma of the sigmoid colon. A 36‐year‐old woman visited our hospital, complaining primarily of vomiting and abdominal pain. Abdominal CT scan showed the typical finding of intussusception. An emergency colonoscopy revealed that the invaginated colon with a polypoid mass was protruding into the descending colon. A gastrografin enema showed the invaginated bowel segment at the descending colon. We performed endoscopic polypectomy and then hand‐assisted laparoscopic reduction. The pathological finding showed tubular adenoma. Laparoscopy is a diagnostic or therapeutic tool for selected cases of adult intussusception. Benign tumor is one of the causes of intussusception in adults and a good indication for laparoscopic surgery.